Gut microbiota shifts favorably with delivery of handwashing with soap and water treatment intervention in a prospective cohort (CHoBI7 trial) - Shirajum Monira; Indrajeet Barman; Fatema Tuz Jubyda; Sk. Imran Ali; Aminul Islam; Kazi Mohammad Zillur Rahman; Mahamud-ur Rashid; Fatema-Tuz Johura; Marzia Sultana; Fatema Zohura; Sazzadul Islam Bhuyian; Tahmina Parvin; et al. (BMC, 2023)
Abstract Background Cholera can result in the expulsion of important microbiota from the gut and result in death if left untreated. The disease transmits mainly via drinking water carrying Vibrio cholerae; and household contacts (HHC) of cholera patients are at elevated risk during the first week of infection. The gut microbiota profiles of HHC-children of cholera patients at Dhaka city slums were investigated before (day 0) and after (day 8) delivery of chlorinated water as part of the major study 'CHoBI7 trial (cholera-hospital-based intervention for 7 days)'. Result Results of sequencing and analysis of bacterial community DNA revealed the predominance of two bacterial phyla: Bacteroidetes and Firmicutes at day 0 with a relative abundance of 62 ± 6 (mean ± SEM%) and 32 ± 7, respectively. The pattern reversed at day 8 with a decreased relative abundance of Bacteroidetes (39 ± 12; p = 0.034) and an increased abundance of Firmicutes (49 ± 12; p = 0.057). Of 65 bacterial families confirmed at day 0, six belonging to Proteobacteria including Vibrionaceae disappeared at day 8. Interestingly, the relative abundance of four Firmicutes families-Lachnospiraceae, Bifidobacteriaceae, Clostridiaceae, and Ruminococcaceae was increased in all five study children at day 8. Conclusion The observed exclusion of pathogenic Proteobacteria and enhancement of beneficial Firmicutes in the gut of children delivered with chlorinated water as part of WASH intervention reflect a great promise of the CHoBI7 program in preventing cholera and improving child health.